PLANETARY MONITORING - THE WAY TO FINDING-OUT OF THE REASONS OF CHANGE OF THE CLIMATE - Teifel, V.G. (Recent Contributions to Physics, 2008)
The problems and tasks of the planetary monitoring consisted of regular observations and studies of the processes in the atmospheres of the planets are considered briefly. The main goal of them is to estimate the cosmic factors role in the global climatic changes on the Earth and other planets.